Inversin correlates with the malignant phenotype of non–small cell lung cancer and promotes the invasiveness of lung cancer cells - Gui-Yang Jiang; Yong Zhang; Xiu-Peng Zhang; Xu-Yong Lin; Juan-Han Yu; En-Hua Wang (Tumor Biology)
Inversin, encoded by NPHP2, is one of the 10 NPHP proteins known to be involved in nephronophthisis (an autosomal recessive cystic kidney). Although the previous reports showed that inversin played an important role in embryonic development and renal diseases, its function in cancer was not revealed clearly so far. As measured by immunohistochemical staining, inversin was highly expressed in the cytoplasm of lung cancer samples (63.4%, 161/254) compared with adjacent normal lung tissues (22.0%, 11/50, p  < 0.01). Moreover, its expression was positively correlated with differentiation ( p  = 0.014), tumor node metastasis staging ( p  = 0.007), and lymph node metastasis ( p  = 0.020). The overall survival of non–small cell lung cancer patients with inversin positive expression (45.41 ± 1.800 months) was significantly reduced compared with those with inversin negative expression (51.046 ± 2.238 months, p  = 0.042). Consistently, we found that the invasion capacity of A549 cells transfected with inversin was significantly stronger than that of control cells ( p  < 0.05), while inversin siRNA-treatment significantly reduced cell invasion in H1299 cells ( p  < 0.05). Additionally, we demonstrated that inversin could upregulate the expression of N-cadherin, Vimentin, matrix metalloproteinase-2, and matrix metalloproteinase-9. Collectively, these results indicated that inversin might promote the tumorigenicity of lung cancer cells and serve as a novel therapeutic target of non–small cell lung cancer.